Access To Justice of Citizenship Rights for Stateless Indonesian Migrant Workers’ Children In Sarawak, Malaysia - Yayan Sopyan (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
As one of the countries that ratified the United Nations Convention on the Rights of the Child in 1990 which was subsequently promulgated into the Child Protection Act, Indonesia is still unsuccessful in protecting children. This mainly occurs in the context of protection illegal migrant workers’ children who were born in the country where their parents work. In Sarawak, Malaysia, for instance, there are 43,445 stateless children. This study aims to portray the stateless children in Sarawak, Malaysia, and the efforts of the Indonesian government to protect their right to access justice. This research is normative-qualitative with observations and in-depth interviews with consultant general staff and Indonesian volunteers In Sarawak as one of the main research methods. The results of this study indicate that stateless condition makes it possible for the children to get other rights, such as education. Meanwhile, the Indonesian government has already made regulations and efforts to provide access to basic human rights for children of stateless migrant workers, including itsbat nikah abroad to legalize unregistered marriage among workers. However, it has not been fully successful because the problems are so complex that it needs to involve several parties, especially the Malaysian government, and plantation owners as employers of the migrant workers. Likewise, harder and more coordinated efforts are also needed to fulfill their citizenship right. (Sebagai salah satu negara yang meratifikasi Konvensi PBB tentang Hak Anak pada 1990 dan kemudian dikristalkan menjadi Undang-undang Perlidungan Anak, Indonesia ternyata belum sepenuhnya berhasil melindungi hak-hak anak. Ini utamanya berlaku dalam konteks perlindungan terhadap anak para buruh migran yang lahir dan tinggal di negara tempat orang tuanya bekerja. Di Sarawak, Malaysia, ada 43.445 anak-anak tanpa kewarganegaraan. Penelitian ini bertujuan memotret kondisi anak buruh migran ilegal tanpa kewarganegaraan di Serawak, Malaysia, serta menjelaskan upaya pemerintah Indonesia untuk melindungi hak-hak mereka. Penelitian ini bersifat normatif-kualitatif dengan observasi dan wawancara mendalam kepada pegawai Konsulat Jenderal dan relawan Indonesia sebagai salah satu metode penggalian data utamanya. Hasil dari penelitian ini menunjukkan bahwa status tanpa kewarganegaraan menghalangi anak-anak tersebut mengakses hak-haknya yang lain, semisal pendidikan. Sementara itu, pemerintah Indonesia sudah memiliki beberapa aturan tertulis dan berupaya memberikan akses keadilan bagi anak para buruh migran tersebut, termasuk melalui program itsbat nikah di luar negeri. Namun demikian, situasi belum sepenuhnya terkendali karena permasalahan yang begitu kompleks dan mengharuskan keterlibatan banyak pihak, utamanya pemerintah Malaysia dan para pemilik perkebunan. Perlu juga dilakukan upaya yang lebih keras dan terkordinasi agar hak-hak tersebut dapat terpenuhi.)